Emerging role of long non-coding RNAs in endothelial dysfunction and their molecular mechanisms - Ravichandran Jayasuriya (Elsevier, 2022)
Long non-coding RNAs (lncRNAs) are the novel class of transcripts involved in transcriptional, post-transcriptional, translational, and post-translational regulation of physiology and the pathology of diseases. Studies have evidenced that the impairment of endothelium is a critical event in the pathogenesis of atherosclerosis and its complications. Endothelial dysfunction is characterized by an imbalance in vasodilation and vasoconstriction, oxidative stress, proinflammatory factors, and nitric oxide bioavailability. Disruption of the endothelial barrier permeability, the first step in developing atherosclerotic lesions is a consequence of endothelial dysfunction. Though several factors interfere with the normal functioning of the endothelium, intrinsic epigenetic mechanisms governing endothelial function are regulated by lncRNAs and perturbations contribute to the pathogenesis of the disease. This review comprehensively addresses the biogenesis of lncRNA and molecular mechanisms underlying and regulation in endothelial function. An insight correlating lncRNAs and endothelial dysfunction-associated diseases can positively impact the development of novel biomarkers and therapeutic targets in endothelial dysfunction-associated diseases and treatment strategies.